Screening For Pre-Malignant Conditions in The Oral Cavity of Chronic Tobacco Chewers - Mahawar, Priyanka; Anand, Shweta; Sinha, Umesh; Bansal, Madhav; Dixit, Sanjay (National Journal of Community Medicine, 2011)
Oral cancer is a major health problem in tobacco users all over the world. It is one of the ten most common cancers in the world. Oral cancer is almost always preceded by some type of precancerous lesion. The precancerous lesions can be detected up to 15years, prior to their change to an invasive carcinoma. It usually affects between the ages of 15 and 40 years. It may be triggered by factors like frequency and duration of tobacco consumption, alcohol, poor oral hygiene etc. This study was conducted primarily to screen chronic tobacco chewers for the presence of oral pre-malignant conditions and secondly to educate them about the hazards of tobacco and motivate them to quit the habit. This was a cross sectional study conducted at Badi gawaltoli area of Indore. Tobacco chewers using tobacco for more than 5yrs were included in the study. Chronic tobacco chewers were screened for oral pre-malignant lesions followed by an educational intervention about the harmful effects of tobacco. Two follow ups were made to motivate them to quit the habit and to get treatment for their lesions. An open ended semi-structured questionnaire was administered to chronic tobacco chewers to assess their habit of tobacco chewing, smoking, their knowledge regarding lesions in their mouth, hazards of tobacco and any cessation efforts. Among the 80 identified chronic tobacco chewers, 60 were males and 20 were females. Lesions such as leukoplakia, erythroplakia and oral sub-mucosal fibrosis were found in 10 females (50%) and 24 males (40%).